The significance of isolated de novo red patches in the bladder in patients referred with suspected urinary tract cancer: Results from the IDENTIFY study - Sinan Khadhouri; Kevin Gallagher; Kenneth R. MacKenzie; Taimur T. Shah; Chuanyu Gao; Eleanor Zimmermann; Miles Mannas; Taeweon Lee; Giancarlo Marra; Juan Gomez Rivas; Gautier Marcq; Mark A. Assmus; et al. (BJUI Compass)
Abstract Objectives To assess the contemporary malignancy rate in isolated de novo red patches in the bladder and associated risk factors for better selection of red patch biopsy. Patients Patients from the IDENTIFY dataset; Patients referred to secondary care with suspected urinary tract cancer and found to have isolated de novo red patches on cystoscopy. Methods We reported the unadjusted cancer prevalence in isolated de novo red patches that were biopsied; multivariable logistic regression was used to explore cancer‐associated risk factors including age, sex, smoking, type of haematuria, LUTS, UTIs and a suspicious‐looking red patch (as reported by the cystoscopist). Sub‐analysis of these by clinical role and experience was performed. Results A total of 1110 patients with isolated de novo red patches were included. 41.5% (n = 461) were biopsied, with a malignancy rate of 12.8% (59/461), which was significantly higher in suspicious versus non‐suspicious red patches (19.1% vs. 2.81%, p < 0.01). There was a significant association between bladder cancer and age (OR 1.04, 95% CI 1.01–1.07, p = 0.01), smoking history (OR 2.62, 95% CI 1.09–6.27, p = 0.03) and suspicious‐looking patch (OR 6.50, 95% CI 2.47–17.1, p < 0.01). The majority of malignancies were in over 60‐year‐olds. Malignancy rates in suspicious versus non‐suspicious red patches did not differ significantly between clinical roles or experiences. Limitations included subjectivity in classifying a suspicious patch and selection bias as not all patches were biopsied. Conclusions Many patients still undergo unnecessary biopsies under general anaesthetic for isolated de novo red patches. Clinicians should consider the patient's age, smoking status and how suspicious‐looking the patch is, before deciding on surveillance versus biopsy to improve cancer diagnostic yield.